Complex and Cascading Triggering of Submarine Landslides and Turbidity Currents at Volcanic Islands Revealed From Integration of High-Resolution Onshore and Offshore Surveys - Clare, Michael A.; Le Bas, Tim; Price, David M.; Hunt, James E.; Sear, David; Cartigny, Matthieu J. B.; Vellinga, Age; Symons, William; Firth, Christopher; Cronin, Shane (Frontiers in Earth Science, 2018)
Submerged flanks of volcanic islands are prone to hazards including submarine landslides that may trigger damaging tsunamis and sediment-laden seafloor flows (called ‘turbidity currents’). These hazards can break seafloor infrastructure which is critical for global communications and energy transmission. Small Island Developing States are particularly vulnerable to these hazards due to their remote and isolated nature, small size, high population densities and weak economies. Despite their vulnerability, few detailed offshore surveys exist for such islands, resulting in a geohazard ‘blindspot’, particularly in the South Pacific. Understanding how these hazards are triggered is important; however, pin-pointing specific triggers is challenging as most studies have been unable to link continuously between onshore and offshore environments, and focus primarily on large-scale eruptions with sudden production of massive volumes of sediment. Here we focus on an area with a high volcanic sediment supply, which is also similar to locations (volcanic or not) where human-induced vegetation change over-supplies sediments to coastal margins. We address these issues by integrating the first detailed (2 m x 2 m) bathymetry data acquired from Tanna Island, Vanuatu with a combination of terrestrial remote sensing data, onshore and offshore sediment sampling, and documented historical events. Mount Yasur on Tanna has experienced low-magnitude Strombolian activity for at least the last 600 years. We find clear evidence for submarine landslides and turbidity currents, yet none of the identified triggers are related to major volcanic eruptions, in contrast to conclusions from several previous studies. Instead we find that cascades of non-volcanic events (including outburst floods with discharges of >1000 m3/s, and tropical cyclones), that may be separated by decades, are more important for preconditioning and triggering of landslides and turbidity currents in oversupplied sedimentary regimes such as at Tanna. We conclude with a general model for how submarine landslides and turbidity currents are triggered at volcanic and other heavily eroding mountainous islands. Our model highlights the often-ignored importance of outburst floods, non-linear responses to land-use and climatic changes, and the complex interactions between a range of coastal and tectonic processes that may overshadow volcanic regimes.